Pengembangan Media Pembelajaran Digital Bertema Transportasi Dua Bahasa (Bahasa Indonesia–Arab) untuk Anak Usia Dini menggunakan model R&D - Sekar Wulandari; Rudi Budi Agung; Siti Chodijah; Zahra Aidid (Prosiding SISFOTEK, 2025)
Language is the most important medium of communication for humans, useful as a tool to convey messages from one person to another. One of the popular languages ????among Indonesian people is Indonesian and Arabic. Language learning can be in schools or in science assemblies, in addition to independent memorization methods. With the presence of current technology can assist learning so that learning can be converted into a digital format with the hope of learning being more practical and interesting. This method is an alternative learning method that can encourage children to feel enthusiastic about learning languages ????for early childhood. In this study, we will create a digital learning media for introducing transportation tools in Indonesian and Arabic to broaden children's insight and education about transportation tools in Indonesian and Arabic. The method developed is the EDDIE model, an acronym for Analysis, Design, Development, Implementation and Evaluation. As well as conducting testing of the application that has been created. The results of this digital learning media are expected to help children in learning the names of transportation tools in Indonesian and Arabic.